2017
DOI: 10.5455/javar.2017.d210
|View full text |Cite
|
Sign up to set email alerts
|

Chelating effect of silver nitrate by chitosan on its toxicity and growth performance in broiler chickens

Abstract: Objective: This study was conducted to investigate the chelating effect of silver nitrate (AgNO3) by chitosan on growth performances, hematological and biochemical parameters, and the histopathological structure of the liver and the kidney in broiler chicken. Materials and methods: A total of 192 day-old Cobb 500 strain chicks were randomly assigned to 3 treatments of 64 chicks each. Control group was fed on basal diet without supplement (R0) and the two others groups were fed on rations supplemented with 10 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 23 publications
1
0
0
Order By: Relevance
“…These results indicated that COS treatments had no detrimental or adverse impact on the blood hematological of Mandarah laying hens. These findings are consistent with those that Doriane et al (2017) stated that COS treatments and the control group had no statistically significant influence on the hematological parameters in the broiler. However, our results recorded that treated birds with COS at different levels had insignificantly improved hematological parameters such as RBCs, WBCs, hemoglobin and hematocrit compared to the control group.…”
Section: Discussionsupporting
confidence: 93%
“…These results indicated that COS treatments had no detrimental or adverse impact on the blood hematological of Mandarah laying hens. These findings are consistent with those that Doriane et al (2017) stated that COS treatments and the control group had no statistically significant influence on the hematological parameters in the broiler. However, our results recorded that treated birds with COS at different levels had insignificantly improved hematological parameters such as RBCs, WBCs, hemoglobin and hematocrit compared to the control group.…”
Section: Discussionsupporting
confidence: 93%